Faith and spirituality in the meaning of life of the elderly with Chronic Kidney Disease - Halanna Carneiro Gumarães Bastos Moura; Tânia Maria de Oliva Menezes; Raniele Araújo de Freitas; Fabiana Araújo Moreira; Isabella Batista Pires; Amélia Maria Pithon Borges Nunes; Marta Gabriele Santos Sales
ABSTRACT Objective: to understand faith and spirituality in the meaning of life of the elderly with Chronic Kidney Disease. Methods: a qualitative research based on Viktor Emil Frankl's Logotherapy and Existential Analysis. Twenty elderly people were interviewed between August 2018 and January 2019, between 60 and 79 years old, who underwent dialysis in a private unit, a reference in nephrology in the city of Salvador, Bahia, Brazil. Results: two categories of analysis emerged: Meaning of faith in the lived of the elderly with Chronic Kidney Disease; Faith as a forerunner of the meaning of life. Final considerations: faith and spirituality were understood as a fundamental foundation in the search for the meaning of the study participants' lives, besides unveiling itself as an important strategy of resilience to the experienced of the elderly person with Chronic Kidney Disease.